On some particular solutions of the Chebyshev's equation by means of ?? Discrete Fractional Calculus Operator - İnç, Mustafa; Yilmazer, Resat (Natural Sciences Publishing, 2016)
In this work, we acquire some new particular solutions of the homogeneous and nonhomogeneous Chebyshev's equations (CE) by using discrete fractional nabla operator ?? (0 < ? < 1). © 2016 NSP.
Keywords: Chebyshev equation; Discrete fractional calculus; Nabla operator